Adopting internal marketing practices in SME’s : case study of state of setif - Bensedira, Ammar (Finance and Business Economies Review, 2020)
This research aims to highlight the extent of adopting internal marketing practices in SMEs, and the researcher in this study relied on two types of data, the first type based on books, studies and previous research, and the second was represented in the field study that included the design and distribution of form With the aim of collecting data from SMEs workers in The State of Setif as the study's stakeholders. Some of the basic concepts of internal marketing, its specifics in SMEs, as well as the basic activities of internal marketing were reviewed, in the end, and the conclusion was finally reached that there was a difference in the level of adoption of internal marketing in SMEs due to factors Personal and institutional.